Detection of clinically occult primary tumours in patients with cervical metastases of unknown primary tumours: comparison of three-dimensional THRIVE MRI, two-dimensional spin-echo MRI, and contrast-enhanced CT. Issue 4 (April 2018) - Yoo, M.G.; Kim, J.; Bae, S.; Ahn, S.S.; Ahn, S.J.; Koh, Y.W.
Abstract : Aim: To evaluate and compare the utility of contrast-enhanced three-dimensional (3D) T1-weighted high-resolution isotropic volume examination (THRIVE), spin-echo (SE) T1-weighted magnetic resonance imaging (MRI), and computed tomography (CT) for detecting clinically occult primary tumours in patients with cervical lymph node metastases. Materials and methods: Seventy-three consecutive patients with tumours that went undetected during endoscopic or physical examinations underwent preoperative contrast-enhanced CT and MRI (SE and 3D THRIVE) after gadolinium injection. Guided biopsy results served as reference standards. The diagnostic performances of the imaging techniques were compared with McNemar's tests. Results: Primary tumours were identified in 59 (80.8%) of the 73 patients after surgery. Of these, 36 were found in the palatine tonsil, 11 in the base of the tongue, seven in the nasopharynx, and five in the pyriform sinus. The sensitivity (72.9%) and accuracy (71.2%) of 3D THRIVE for detecting primary tumours were higher than were those of SE T1-weighted MRI (49.2% and 53.4%, p≤ 0.002) or CT (36.4% and 46.4%, p≤ 0.001). The specificities of these techniques did not differ. The diagnostic performance of 3D THRIVE (area under the curve [AUC]=0.681) for detecting tumours did not differ from that of SE T1-weighted MRI or CT (AUC=0.671 and 0.608, p> 0.05). Conclusion: 3D THRIVE was more sensitive at detecting primary tumours than was SE T1-weighted MRI or CT in patients with cervical metastases of unknown primary tumours. This sequence may improve biopsy and therapeutic planning in these patients. Highlights: Preop localization of the primary tumour is critical in patients with neck LN metastases. 3D THRIVE is more sensitive at detecting primary tumours than is SE T1-weighted MR. Using the 3D THRIVE sequence may improve biopsy targeting and therapeutic planning.